2018
DOI: 10.1364/oe.26.014066
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of application-driven network slicing and orchestration in optical/packet domains: on-demand vDC expansion for Hadoop MapReduce optimization

Abstract: Nowadays, it is common for service providers (SPs) to leverage hybrid clouds to improve the quality-of-service (QoS) of their Big Data applications. However, for achieving guaranteed latency and/or bandwidth in its hybrid cloud, an SP might desire to have a virtual datacenter (vDC) network, in which it can manage and manipulate the network connections freely. To address this requirement, we design and implement a network slicing and orchestration (NSO) system that can create and expand vDCs across optical/pack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…I n t he s pecific context of flexi-grid o ptical n etworks, t he a uthors i n [ 34] addressed the problem of deploying virtual networks (i.e., tenants) on top of an elastic optical network to be used for inter-connecting a myriad of remote DCs. Moreover in [35], the authors demonstrated a solution for orchestrating both cloud and network resources for inter-connecting multiple DCs over a packet and optical transport infrastructure.…”
Section: B Resource Allocation In Multi-dc Infrastructuresmentioning
confidence: 99%
“…I n t he s pecific context of flexi-grid o ptical n etworks, t he a uthors i n [ 34] addressed the problem of deploying virtual networks (i.e., tenants) on top of an elastic optical network to be used for inter-connecting a myriad of remote DCs. Moreover in [35], the authors demonstrated a solution for orchestrating both cloud and network resources for inter-connecting multiple DCs over a packet and optical transport infrastructure.…”
Section: B Resource Allocation In Multi-dc Infrastructuresmentioning
confidence: 99%
“…IoT have increased its usage and attracted more due to inventions of smart devices information process [7]. Problem of reducing the IoT loss in every life cycle is achieved through analyzing the data efficiently by mining rules and characteristics on IoT [8]. The advanced precision mathematical technique has to be enhanced in the present cloud IoT model to upgrade the traditional IoT methods [9].…”
Section: Related Workmentioning
confidence: 99%
“…Further efficiency of devices are calculated using how less energy require to process for computing the data. If the devices have more computation capacity it consume more energy, time and memory for processing [8,9]. When the mobile devices consume more energy, it will abbreviate battery life and leads to emit greenhouse gases.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning flexi-grid optical networks, in [16], the problem of the interconnecting myriad of DCs by virtual networks on top of an elastic optical network has been tackled. Moreover, in [15], a combined orchestration process for both cloud and and network resources to interconnect multiple DCs over a packet and optical transport infrastructure has been proposed. As far as our knowledge, all these approaches focus on optimizing the resource consumption and do not consider the impact of the network delay which is becoming an important requirement when deploying network services across distributed DCs [17].…”
Section: Introductionmentioning
confidence: 99%